Can Phone-Based Motivational Interviewing Improve Medication Adherence to Antiplatelet Medications After a Coronary Stent Among Racial Minorities? A Randomized Trial - Palacio, Ana M. (J Gen Intern Med, 2014)
BACKGROUND: Minorities have lower adherence to cardiovascular medications and have worst cardiovascular outcomes post coronary stent placement OBJECTIVE: The aim of this study is to compare the efficacy of phone-delivered Motivational Interviewing (MINT) to an educational video at improving adherence to antiplatelet medications among insured minorities. DESIGN: This was a randomized study. PARTICIPANTS: We identified minorities with a recently placed coronary stent from an administrative data set by using a previously validated algorithm. INTERVENTIONS: MINT subjects received quarterly phone calls and the DVD group received a one-time mailed video. MAIN MEASURES: Outcome variables were collected at baseline and at 12-month post-stent, using surveys and administrative data. The primary outcome was antiplatelet (clopidogrel and prasugrel) adherence measured by Medication Possession Ratio (MPR) and self- reported adherence (Morisky score). We also measured appropriate adherence defined as an MPR ≥ 0.80. KEY RESULTS: We recruited 452 minority subjects with a new coronary stent (44 % Hispanics and 56 % Black). The patients had a mean age of 69.5 ± 8.8, 58 % were males, 78 % had an income lower than $30,000 per year and only 22 % had achieved high school education or higher. The MPR for antiplatelet medications was 0.77 for the MINT group compared to 0.70 for the DVD group (p < 0.05). The percentage of subjects with adequate adherence to their antiplatelet medication was 64 % in the MINT group and 50 % in the DVD group (p < 0.01). Self-reported adherence at 12 months was higher in the MINT group compared to the DVD group (p < 0.01). Results were similar among drug-eluting stent (DES) recipients. CONCLUSIONS: Among racial minorities, a phone-based motivational interview is effective at improving adherence to antiplatelet medications post coronary stent placement. Phone-based MINT seems to be a promising and cost-effective strategy to modify risk behaviors among minority populations at high cardiovascular risk.